Predictors of Vision Loss after Surgery for Macula-Sparing Rhegmatogenous Retinal Detachment. (3rd August 2022) - Gopal, Anand; Starr, Matthew; Obeid, Anthony; Ryan, Ed; Ryan, Claire; Ammar, Michael; Patel, Luv; Forbes, Nora; Capone, Antonio; Emerson, Geoff; Joseph, Daniel; Eliott, Dean; et al.
Abstract: Purpose: To determine factors associated with loss of good vision (defined as Snellen visual acuity [VA] < 20/40) after surgery among eyes presenting with macula-on primary rhegmatogenous retinal detachment (RRD) with initial VA ≥20/40. Methods: Multicenter, retrospective, cohort study of eyes undergoing scleral buckle (SB), pars plana vitrectomy (PPV), or combined pars plana vitrectomy/scleral buckle (PPV/SB) for non-complex macula-on RRD with initial VA ≥20/40. Results: Among 646 eyes with macula-on RRDs with initial VA ≥20/40, 106 (16.4%) had VA <20/40 (i.e. lost good vision) at final follow-up. Eyes losing good vision had slightly worse pre-operative logMAR VA (mean 0.15 ± 0.10 [20/28]) compared to eyes that preserved good vision (mean 0.11 ± 0.10 [20/26]) (p = 0.004). RRDs extending greater than 6 clock-hours were more likely to lose good vision than smaller detachments (multivariate OR 4.57 [95% CI 1.44–14.51]; p = 0.0099). Compared to eyes repaired with SB alone, eyes undergoing PPV (multivariate OR 7.22 [95% CI 2.10–24.90]; p = 0.0017) or PPV/SB (multivariate OR 10.74 [95% CI 3.20–36.11]; p = 0.0001) were each more likely to lose good vision. Eyes requiring further RRD-related (multivariate OR 8.64 [95% CI 1.47–50.66]; p < 0.017) and non-RRD related vitreoretinal surgery (multivariate OR 14.35 [95% CI 5.39–38.21]; p < 0.0001) were more likely to lose good vision. Conclusion: Among macula-on RRDs, loss of good vision was associated with worse vision on presentation, vitrectomy-based procedures, greater extent of detachment, and lack of single surgery success. Understanding predictors of visual outcome in macula-on RRD repair may guide pre-operative counseling regarding visual prognosis.